[CII] emission and star formation in late-type galaxies - Pierini, Daniele; Leech, K.J.; Tuffs, R.J.; Völk, Heinrich J. (Astrophysics and space science, 2001)
A linear correlation between the ratio of the[CII($$^{\text{2}}$$P$$_{3/2}$$→$$^{\text{2}}$$P$$_{1/2}$$)] line intensity to the [$$^{{\text{12}}}$$CO(J:1 →0)] line emission, I$$_{{\text{CII}}}$$/I$$_{{\text{CO}}}$$and the $${\text{H}}_\alpha$$equivalent width (EW) is found, over the range 2-71 Å in $${\text{H}}_\alpha$$EW, for a sample of 21late-Type= galaxies. The latter is comprised of an optically selected sample of 12 normal Virgo Cluster spiral galaxies with [CII] detections obtained by us with ISOLWS, plus nine late-Type= galaxies with higher star formation rates (SFRs), for which [CII] data and, especially,$${\text{H}}_\alpha$$EW data are available in the literature. As a result we infer I$$_{{\text{CII}}}$$/I$$_{{\text{CO}}}$$to be a reliable tracer of the current mass-normalized global SFR for non-starburst spiral galaxies. Moreover, the ratio of the [CII] line to the total far-infrared (FIR) continuum intensity, I$$_{{\text{CII}}}$$/I$$_{{\text{FIR}}}$$, is found to decrease from ∼0.5% to ∼0.1% with decreasing SFR which we propose is due to a `[CII]-quiet' component of I$$_{{\text{FIR}}}$$from dust heated by the general interstellar radiation field (ISRF). The more `quiescent' galaxies in the sample have values of I$$_{{\text{CII}}}$$/I$$_{{\text{CO}}}$$different from those observed in `compact' Galactic interstellar regions. Their [CII]-emission is interpreted to be dominated by diffuse regions of the interstellar medium (ISM). For normal `star-forming' galaxies the diffuse component of the [CII] emission is estimated to account for at least 50% of the total.
Gesehen am 19.11.2020